(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Filipinos are always on the go, though there are dining restaurants all around, sometimes, or most often, they prefer affordable and quick orders of fast food. It is often visible at birthday parties or cheap group meals, and by observation, which can tell that their service will always be in demand, especially in the Philippines, where most cannot afford luxury in expensive restaurants. Respondents had an effect on the portion size of food and had a problem with the speed of service, employee greetings, and the sound level of the branch and in giving information to the customer. Most of the respondents had a problem with their manager’s feedback. Findings show that the respondents have an equal result. They do not have any problem with their professionalism but are having a problem with going to work with excitement. McDonald’s should make their food servings bigger, like “what you see is what you get” on their menu. Employees should entertain the customer politely and always keep smiling in front of the customer so that the customer won’t hesitate to ask the employee something. McDonald’s should provide a relaxing playlist so that the customer can relax while dining. McDonald’s employees should exercise every morning before they open the store so that they will not get exhausted and be more energetic. Employees of McDonald’s should be committed to what they’re doing in their workplace for them to achieve customer satisfaction.